PENGARUH LIKUIDITAS, EARNINGS GROWTH, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP ABNORMAL RETURN SAHAM INDEKS LQ 45 - Chendrawan, Toni S (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2012)
The Influence of Liquidity, Earnings Growth, Leverage and Firm Size to Abnormal Return. The purposeof this research to analize price response on the market based on firms fundamental information. Theindicator which used at firms value variable is price reaction through abnormal return at financialreport publication date. Verificative and dascriptive methods were used as reseach desaign. Analysisunit is firms who joined on LQ 45. The sampling taking methods is purposive sampling whit criteriathe firms who stayed on LQ 45 group during research periode, so that the sample which use is 24firms. The data which needed on this resaarch is financial, acccountance profit, market capitalized,stock price and IHSG during financial report publication date. And for technic of analize we usemultiple regression, which hard purpose to know the impact of firms fundamental information toabnormal return of financial report publication date. The result of this research is between of allindependent variable which had significant impact to abnormal return is leverage.